The pleiotropic effects of Innexin genes expressed in Drosophila glia encompass wing chemosensory sensilla. Issue 10 (30th June 2019) - Raad, Hussein; Robichon, Alain
Abstract: The neuroanatomy of Drosophila wing chemosensilla and the analysis of their sensory organ precursor cell lineage have demonstrated that they are surprisingly related to taste perception. The microarchitecture of wing bristles limits the use of electrophysiology methods to investigate wing chemosensory mechanisms. However, by monitoring the fluorescence of the complex calcium/GCaMP, calcium flux triggered upon tastant stimulation was observed within sensilla aligned along the wing anterior nerve. This string of fluorescent puncta was impaired in wings of Innexin 2 ( Inx2 ) mutant flies; although it is unclear whether the Innexin proteins act at the level of the wing imaginal disc, adult wing and/or at both levels. Glial cells known to shelter Innexin(s) expression have no documented role in adult chemosensory sensilla. Our data suggest that Innexin(s) are likely required for the maturation of functional wing chemosensilla in adulthood. The unexpected presence of most Innexin transcripts in adult wing RNAseq data set argues for the expression of Innexin proteins in the larval imaginal wing disc that are continued in wing chemosensilla at adulthood. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available as supporting materials and includes the electronic lab notebook. Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki . Abstract : Drosophila wing chemosensilla are surprisingly related to taste perception. This demonstrates that Drosophila wing is a chemodetection organ whose specific roles to probe compounds in ecological niches is yet understudied. Using a transgenic fly to monitor the calcium flux triggered upon tastant molecules within wing sensilla, we show that impaired responses occured in wings of mutant Innexin2. Moreover, we report that most of members of Innexin family are expressed in adult wing leading to the conclusions that gap junction proteins or hemichannels are active at this stage.